Analysing Collaborative Processes and Interaction Patterns in Online Discussions - Blake, Canan; Scanlon, Eileen (Proceedings of the International Conference on Networked Learning, 2012)
This paper deals with collaborative, networked learning in a graduate distance learning course. We are interested in understanding how learning is affected by the quality of collaborative processes and the patterns of interaction in collaborative online discussion environments. For the purposes of this paper we are focusing on the interactions and collaborative processes occurring in an asynchronous online seminar which is about the design of teaching/learning software in the context of a science education course. The participants in the study, a total of nine students are mainly science teachers and they took part in this online seminar over a two week period to discuss the design of some selected pieces of software used for teaching and learning of science at various levels of schooling. In our analysis, we used a classification system validated in our earlier work and extended our approach for the purposes of this study using a rating scheme developed for assessing the quality of computer supported collaboration processes by other researchers (see Meier et al., 2007; and Rummel et al., 2011). Content analysis of the contributions to the online seminar showed that the two categories, namely ’acknowledging a fellow student by replying and or referring to their contribution’ and ’motivation of students (indicated by a mention of their individual commitment to group task)’ were the biggest categories. The frequency of ’joint knowledge building category’ in this analysis indicates that students are committed to the task. During the activity they presented reports on their analyses with an aim to critically review the issues and themes arising form these analyses. When we compared this online seminar to a comparable one in the previous year, we noticed that both acknowledgment and motivational categories were much smaller. In addition to content analysis, we carried out an interaction analysis of the first online seminar to identify the patterns of relationship between students and visualise the relationship by using the connections between members. This study may indicate the importance of motivation/individual commitment of students during a collaborative task and we are in the process of analysing other conferences in the same course to see the effect of motivation on the quality of collaborative learning/processes and the interaction patterns in the online seminar.